Femtosecond laser‐written waveguides in thulium‐doped fluoroindate glass for S‐band amplification. Issue 7 (1st March 2014) - Elan, F.; Olivero, M.; Falcão‐Filho, E.L.; de Araújo, C.B.; Messaddeq, Y.; Gomes, A.S.L.
Abstract : Channel waveguides were written in a fluoroindate bulk glass containing thulium, with a femtosecond laser operating at 800 nm, 100 fs pulses and a repetition rate of 1 kHz. Formation of waveguides occurred for average powers from 1 to 8 mW (corresponding to energies of 1–8 μJ) and scan velocities in the range of 0.1–4 mm/s. Passive optical characterisation included visual inspection by an optical microscope, insertion loss and mode profile. Active characterisation was performed by co‐propagating pumping in a dual‐pump scheme that included an 808 nm and a 1054 nm laser diode for an efficient inversion of the 3 H4 level, which is responsible for stimulated emission in the 1460–1530 nm spectral range. Preliminary tests show a net gain of 2.5 dB at 1487 nm, for straight waveguides 1 cm long. Applications include the fabrication of lossless components working in the S‐band region of the optical communication spectrum.